2021
DOI: 10.1177/20503121211031428
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and chronic obstructive pulmonary disease in Moroccan adults: Evidence from the BOLD study

Abstract: Objective: The Moroccan cross-sectional study aimed to investigate obesity in association to chronic obstructive pulmonary disease in Fez city. Methods: A cross-sectional survey was carried out in Moroccan adults. Anthropometric and spirometry measurements were performed using standardized guidelines. Results: Among the 744 participants, 53.9% of were women, with a mean age of 55.27 years (SD = 10.29). Nearly all women declared themselves to be never smokers, while 21% of men were current smokers. Overall, chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…23–25 COPD is a major public health problem in Morocco. 15 , 26 , 27 Our study revealed a prevalence of 6.7%. This value is lower than that reported by a previous national study, which reported a prevalence of 12.6%.…”
Section: Discussionmentioning
confidence: 46%
“…23–25 COPD is a major public health problem in Morocco. 15 , 26 , 27 Our study revealed a prevalence of 6.7%. This value is lower than that reported by a previous national study, which reported a prevalence of 12.6%.…”
Section: Discussionmentioning
confidence: 46%
“…Benslimane et al observed a 25% reduction in the prevalence of COPD in obese individuals. 38 In addition, Atassi et al found a statistically significant association between low socio-economic status and the development of COPD. 39 Taken together, these data demonstrate the importance of other risk factors in the development of COPD among non-smokers.…”
mentioning
confidence: 99%